Estrategias metodológicas y su relación con el aprendizaje de la técnica del arquero en los deportistas de fútbol del Club Padre Juan Agnoletto en el 2022 - Delgado Briones, Mayelin Alicia (2022)
This work has considered a theoretical but above all methodological inspection for: Objective: to analyze the relationship that methodological strategies have with the learning of the goalkeeper's technique for sports adaptation in the soccer students of the Club Deportivo Padre Juan Agnoletto; through a broad theoretical inspection regarding the considerations that must be taken to talk about the Physical Education program and its possible impact on the physical development of adolescents in the 1st year of high school of the Francisco Huerta Rendón Educational Unit of the Babahoyo canton. Methodology: The sample was made up of a selection of 80 students, with a mean age between 9.47 ± 0.043 in a range between 8 - 17 years. Results: Through the application of the surveys, it was determined what strategies are being applied in the training of the students of the Sports Club. The survey was applied to 50% of the total population registered in it. The interpretation allows the presentation of a work guide to highlight the training capabilities of goalkeepers, but also complements the collaborative work of all the participants trained in the Sports Club.